Biochemistry concepts and connections - Appling, Dean Ramsay; Anthony-Cahill, Spencer J.; Mathews, Christopher K., 1937- (Pearson Education Limited, 2016)
Biochemistry: Concepts and Connections engages students in the rapidly evolving field of biochemistry, better preparing them for the challenges of 21st century science through quantitative reasoning skills and a rich, chemical perspective on biological processes. This concise first edition teaches mixed-science-majors the chemical logic underlying the mechanisms, pathways, and processes in living cells through groundbreaking biochemical art and a clear narrative that illustrates biochemistry's relation to all other life sciences. Integration of biochemistry's experimental underpinnings alongside the presentation of modern techniques encourages students to appreciate and consider how their understanding of biochemistry can and will contribute to solving problems in medicine, agricultural sciences, environmental sciences, and forensics.